Pressure-point-garments: haptic stimulation of the body enabled through a fashionable 3D-textile interface - Dominique Almendariz; Nikolaj Munk Nielsen; Laura Deschl (Communications in Development and Assembling of Textile Products)
Developments in textile and fiber engineering have allowed the development of functional clothing such as protective wear, sportswear, and medical clothing. Stimulating pressure points on the skin has a wide range of applications in manual therapy – both to eliminate functional disorders in the musculoskeletal system and to relieve pain. An acupressure-like effect can be achieved when the practitioner or the person pressures the skin with the thumb on specific pressure-points on the body. So far, there have not been any product solutions which combine (full)-body garments with an acupressure-like effect. Understanding textiles as a grid which holds pressure balls in place and making use of fiber and textile technologies for industrial knitting has enabled “trykk.” to develop four pressure-point-garments with different textile variables. The purpose of the garment is to substitute the mechanical stimulation of the acupressure-like thumb on the skin through a patent-pending 3-dimensional textile-body interface which consists of a flexible textile grid and small marble-sized semi-precious stone balls. This paper describes a study set-up where the four prototypes in five different haptic use-scenarios are compared to the average force applied in an acupressure-like intervention. Besides, data of the likeability (satisfaction) regarding the four distinctive textiles were obtained. Results demonstrated a comparable performance of the prototypes in four out of five use case scenarios. Textile variables significantly altered users’ interest in the garments, yet had no significant effect on the technical performance and the perceived intensity of stimulation.